The different faces of multilinguality - Gabryś-Barker, Danuta (Linguarum Arena, 2025)
One of the important factors in foreign language teachers’ development is their ability to reflect on educational processes they are involved in and also on themselves as not only teachers but also language learners and users (Gabryś-Barker 2012). The present paper discusses the importance of understanding the different dimensions of the concepts of multilingualism and multilinguality in the educational context and more precisely, in foreign language teacher training. The overview of studies that were carried out as a way of raising awareness of future teachers of English and other foreign languages is presented here as a part of teacher training programmes run at the University of Silesia within the module of research project. The conclusions and implications drawn from the research exemplify how future teachers’ multilingual awareness can contribute not only to their individual multilinguality but foremost to their professional development as teachers of multilingual learners.